Thermopower engineering of Bi2Te3 without alloying: The interplay between nanostructuring and defect activation - Bae, Changdeuck; Boehnert, Tim; Gooth, Johannes; Lim, Seulky; Lee, Seonhee; Kim, Hyunchul; Heimann, Stefan; Schulz, Stephan; Shin, Hyunjung; Nielsch, Kornelius (Semiconductor Science and Technology, 2014)
We report on the interplay between nanostructuring and defect activation in dense polycrystalline Bi2Te3 thin films in terms of the thermopower engineering. The Bi2Te3 thin films were prepared at relatively low temperatures (100-160 °C) by atomic layer deposition and their grains showed different sizes in the range of 50-200 nm according to the deposition temperatures. We monitored the conductivity, Seebeck coefficient, and power factor of all samples from the temperature of 50-400 K. By increasing the growth temperature, remarkably, we observed the gradual defect activation from the nominal p-type to n-type in our binary end compound, Bi2Te3 without any alloying. The present results give us an insight on the optimization of thermoelectric materials not only by nanostructuring (i.e., phonon engineering) but also by controlled defect activation (i.e., electron engineering). © 2014 IOP Publishing Ltd.
CRIS-Team Scopus Importer:2023-03-20
Keywords: atomic layer deposition; thermopower; topological insulators